AKUMULASI LOGAM TIMBAL (Pb) DAN LOGAM TEMBAGA (Cu) DALAM UDANG REBON (Mysis. Sp) DI MUARA SUNGAI PALU - Fujiastuti, Fujiastuti; Said, Irwan; Sakung, Jamaluddin (Jurnal Akademika Kimia, 2013)
The estuary of Palu River is one of river in Palu city which becomes income sources for the local fisherman. The main catch is rebon shrimp (Mysis. Sp). There are many human activities along the Palu River which potentially produce waste that containing heavy metal including lead and copper metal which can contaminate the water. This research aims to find out the content of lead metal (Pb) and copper metal (Cu) which accumulated in rebon shrimp (Mysis. Sp) in the estuary of Palu River. This research used field observation method by taking sample of rebon shrimp (Mysis. Sp) in the estuary of Palu River. The content of lead metal and copper metal inside rebon shrimp (Mysis. Sp) were determined by using Spectro Direct device. Data obtained were analysed descriptively by comparing food standards based on the decree of Directorate General of Drug and Food Control Number 03725/B/SK/VII/89 and SNI 01-2729.1-2006. The research result showed that the content of lead metal inside rebon shrimp (Mysis. Sp) 0.57 mg/kg, which means lead metal has exceeded the specified threshold of food value (0.4 mg/kg). While the content of copper metal inside rebon shrimp (Mysis. Sp) <0.5 mg/kg still below the specified threshold (20 mg/kg).